Immunization associated with primary tumor growth leads to rejection of commonly used syngeneic tumors upon tumor rechallenge. Issue 2 (15th July 2020) - Alicke, Bruno; Totpal, Klara; Schartner, Jill M; Berkley, Amy M; Lehar, Sophie M; Capietto, Aude-Hélène; Cubas, Rafael A; Gould, Stephen E
Abstract : The recent success of multiple immunomodulating drugs in oncology highlights the potential of relieving immunosuppression by directly engaging the immune system in the tumor bed to target cancer cells. Durable responses to immune checkpoint inhibitors experienced by some patients may be indicative of the formation of a T cell memory response. This has prompted the search for preclinical evidence of therapy-induced long-term immunity as part of the evaluation of novel therapeutics. A common preclinical method used to document long-term immunity is the use of tumor rechallenge experiments in which tumor growth is assessed in mice that have previously rejected tumors in response to therapy. Failure of rechallenge engraftment, typically alongside successful engraftment of the same tumor in naive animals as a control, is often presented as evidence of therapy-induced tumor immunity. Here, we present evidence that formation of tumor immunity often develops independent of therapy. We observed elevated rates of rechallenge rejection following surgical resection of primary tumors for four of five commonly used models and that such postexcision immunity could be adoptively transferred to treatment-naïve mice. We also show that tumor-specific cytolytic T cells are induced on primary tumor challenge independent of therapeutic intervention. Taken together these data call into question the utility of tumor rechallenge studies and the use of naïve animals as controls to demonstrate therapy-induced formation of long-term tumor immunity.